Is Phubbing Gendered? Examining The Influence of Neuroticism and Gender in College Students - Rinaldi, Martaria Rizky; Pratiwi, Ratri; Anggawijayanto, Erydani; Kuncoro, M Wahyu; Latue, Devan Gratcio (Universitas Ahmad Dahlan, 2025)
This study examined the relationship between neuroticism and phubbing among university students and explored the moderating role of gender. Guided by the stress and coping model and personality theory, a cross-sectional survey was conducted with 236 Indonesian students (53% female; 85.8% aged 20–23) using validated measures: the Generic Scale of Phubbing and the IPIP-BFM-25 emotional stability subscale. Descriptive analysis showed that phubbing scores were notably right-skewed, with a mean of 53.2 (SD = 17.94) and a higher median of 66.0. Neuroticism significantly predicted phubbing behavior (Estimate = 2.369, SE = 0.120, 95% CI [2.133, 2.605], p < .001), while gender showed no main effect (p = .120) and did not moderate the neuroticism–phubbing relationship (interaction p = .093). Independent t-tests and Mann–Whitney U tests confirmed no significant gender differences in either phubbing or neuroticism levels. These findings suggest that neuroticism is a more robust predictor of phubbing than gender, likely due to differences in emotional regulation. Given the use of convenience sampling and a cross-sectional design, the generalizability of findings is limited. Targeted interventions focusing on emotional coping may be effective in reducing phubbing, especially among individuals high in neuroticism.